OF SOME SPECIFICS IN IMPLEMENTATION OF INTERNATIONAL PRACTICES FOR TECH TRANSFERS OF BIOTECH INNOVATIONS / THE CASE OF THE BULGARIAN UNIVERSITY PLATFORM “VITA PLUS” - A. Vladikov; T. Yosifov (Trakia Journal of Sciences)
The first-of-its-kind University of Plovdiv transdisciplinary project “Vita Plus” is deemed to adopt some positive international practices to initiate and announce that there are researchers at the University of Plovdiv, interested in realizing tech transfers in the field of biotech innovations. Thus, the goal of the present paper is to explain what factors might be crucial to both characterize technological transfer of biotech innovations as successful from University researchers’ viewpoint, and present them to business ventures for commercial purposes. Research methods of the study include data of the most recent thematic study of the World Bank on Bulgaria and analytical reviews of contemporary scientific literature to establish a modern Bulgarian platform for transfer of biotechnological know-hows to bio-based industries in the forthcoming era of bioeconomy. The results of the research are aimed at formation of comparativeanalytical parameters and benchmark indicators for economic valuation of implementation of biotechnological solutions in the emerging Bulgarian circular economy, based on observations at the “Vita Plus” project. Conclusions relate to derivation of a set of recommendations for formation of a new integrated approach for creating a working model for technological transfer of University researches and solutions in real bio-based industrial production through the University platform “Vita Plus”.